2022
DOI: 10.3390/rel13040299
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Program to Reduce Religious Prejudice in Education Settings: A Scoping Review

Abstract: In a plural society, education has an important role in preparing students to be able to live together with differences, including religious differences. Based on the contact hypothesis theory, various intervention programs have been carried out to overcome religious prejudice. This study aims to explore the concept, form, and impact of the interfaith intervention program in reducing religious prejudice in the context of education. The method used was a scoping review following the PRISMA-ScR protocol. Article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
0
5
0
5
Order By: Relevance
“…Sementara itu, faktor lain yakni sebesar 72,4% merupakan variabel lain di luar fundamentalisme beragama dan kecemasan kelompok yang berpengaruh terhadap munculnya prasangka terhadap kelompok homoseksual. Dari beberapa riset terdahulu, faktor yang secara signifikan berpengaruh terhadap prasangka terhadap kelompok lain di antaranya adalah otoritarian sayap kanan (33), dukungan sosial (34), empati (24), kontak antarkelompok (12,35), identitas kelompok (4,36).…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…Sementara itu, faktor lain yakni sebesar 72,4% merupakan variabel lain di luar fundamentalisme beragama dan kecemasan kelompok yang berpengaruh terhadap munculnya prasangka terhadap kelompok homoseksual. Dari beberapa riset terdahulu, faktor yang secara signifikan berpengaruh terhadap prasangka terhadap kelompok lain di antaranya adalah otoritarian sayap kanan (33), dukungan sosial (34), empati (24), kontak antarkelompok (12,35), identitas kelompok (4,36).…”
Section: Hasil Dan Pembahasanunclassified
“…Dalam masyarakat yang majemuk prasangka dan diskriminasi merupakan persoalan dalam relasi sosial terutama terhadap kelompok minoritas (12) seperti homoseksual. Berbagai penelitian terdahulu tentang prasangka terhadap homoseksual telah dilakukan pada konteks Indonesia.…”
unclassified
“…This data suggests that, overall, the university students participating in this study tend to have relatively high levels of ethno-religious prejudice. In essence, students and educational institutions, such as universities, play a crucial and strategic role in reducing social prejudices by equipping individuals with knowledge, attitudes, and competencies to live harmoniously in social diversity (Tondok et al 2022;Sugihartati et al 2020;Bukhori 2017).…”
Section: The Ges and Ethoreligious Prejudice In Indonesiamentioning
confidence: 99%
“…Negative attitudes or prejudice toward outgroups based on social identity, such as ethnicity and religion, can lead to significant detrimental consequences for individuals and society as a whole (Kite et al 2023). Ethnoreligious prejudice has the potential to disrupt social harmony by creating tension and division within communities, pitting different groups against each other, leading to social conflict, tension, and even violence (Hossain 2023;Tondok et al 2022). Furthermore, these intergroup negative attitudes can hinder the realization of inclusive societies where all individuals, regardless of their background, can fully participate and benefit from the community's opportunities and resources (Mayhew and Rockenbach 2021;Saroglou 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this line, various studies (Andreu and Ouhamid 2021) found that in socio-educational settings where intervention programs were implemented, the ability to work together and to communicate in different contexts improved (Tondok et al 2022). In addition, racist behaviors towards cultural diversity were not observed, as these programs were shown to have a positive impact on attitudes towards the outgroup (Paluck and Shepherd 2012), with low levels of prejudice detected among participants (García et al 2003).…”
Section: Introductionmentioning
confidence: 98%